2021
DOI: 10.1101/2021.04.30.442148
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Myofibroblast transcriptome indicates SFRP2+ fibroblast progenitors in systemic sclerosis skin

Abstract: Skin and lung fibrosis in systemic sclerosis (SSc) is driven by myofibroblasts, alpha-smooth muscle actin expressing cells that arise from a variety of cell types in murine fibrosis models. Utilizing single cell RNA-sequencing to examine the transcriptome changes, we show that SSc dermal myofibroblasts arise from an SFRP2/DPP4-expressing progenitor fibroblast population that globally upregulates expression of transcriptome markers, such as PRSS23 and THBS1. Only a fraction of SSc fibroblasts differentiate into… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 86 publications
2
32
1
Order By: Relevance
“…A cluster of preadipocytes (mixed with ASC) express metallothionein genes, and a separate cluster express ISG15 and other IFN-related genes ( Figure 4A ). Finally, we identified several fibroblastic cell populations similar to those recently described in the dermis (Tabib et al, 2021). One population expressing SFRP2, DPP4, and PCOLCE2 is analogous to the PCOLCE+ fibroblast.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…A cluster of preadipocytes (mixed with ASC) express metallothionein genes, and a separate cluster express ISG15 and other IFN-related genes ( Figure 4A ). Finally, we identified several fibroblastic cell populations similar to those recently described in the dermis (Tabib et al, 2021). One population expressing SFRP2, DPP4, and PCOLCE2 is analogous to the PCOLCE+ fibroblast.…”
Section: Resultssupporting
confidence: 66%
“…Comparing non-diabetic, prediabetic and diabetic PWH, myeloid (median percent: 34.1%, 19.3%, 23.7%, respectively; p = 0.23) and lymphoid (median percent: 24.7%, 8.8%, 15.1%, respectively; p = 0.17) proportions were not significantly different (Figure 1E). Age and sex can influence adipocyte function and immune cell populations (Caso et al, 2013;Chang et al, 2018;Huang et al, 2021;Vasanthakumar et al, 2020), but we found no significant differences in cell proportions after stratifying by these factors. Taken together, these data represent the largest single-cell genomic, and first proteogenomic, comprehensive atlas of scWAT, as well as the first characterization of scWAT in persons with diabetes and HIV infection.…”
Section: Heterogeneity Of Cell Populations By Disease Statecontrasting
confidence: 64%
“…Using single‐cell RNA‐seq analysis, we examined gene expression of all enzymatically digested skin cells obtained from 12 patients with dcSSc and 10 healthy control subjects. All subjects have been included in another analysis of fibroblasts in fibrotic skin (19). Patients with dcSSc and control subjects were balanced across sex and age (Supplementary Table 1, available on the Arthritis & Rheumatology website at https://doi.org/10.1002/art.41813/abstract).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study discovered that DPP4expressing fibroblasts are responsible for collagen deposition in dermal scars and inhibition of DPP4 reduced scar formation in a mouse model of wound healing (16). The following studies demonstrated that SFRP2/DPP4 fibroblast subpopulation is the progenitor of fibrogenic fibroblasts in SSc skin (136) and DPP4 activated NF-kB and SMAD signaling through PAR2, leading to the activation of dermal fibroblasts (92).…”
Section: Dpp4 In Systemic Sclerosismentioning
confidence: 87%